Information And Communication Technology Use Among Teacher Education Students In Universities In Kenya - Makori, George; Mwangi, Ndirangu; Ogola, Fredrick (IJSTR Research Publication, 2013)
Information and Communication Technologies (ICTs) which involve the integration of telecommunications, computers as well as various software and audio-visual system are becoming the new educational tools especially in universities. The study sought to investigate the types of ITCs used frequently (on and off campus) among teacher education undergraduates in public and private universities in Kenya. Simple random sampling was used to select 223 fourth year Bachelor of education students. The data was collected using researcher administered questionnaires. Descriptive statistical techniques were used to analyse the data. The findings were presented in tables. The study found out that students frequently used a variety of ICTs such as the internet, computer laboratories and the mobile telephone on and off campus. The study also found out that both private and public universities ha invested substantially on ICT infrastructure for use by their students.
Keywords: Comparative use; ICTs; Teacher Education; Utilization